An Overview of High-energy Ball Milled Nanocrystalline Aluminum Alloys - Gupta, Rajeev Kumar; Murty, B. S.; Birbilis, Nick (Springer International Publishing : Imprint: Springer, 2017)
This book presents a comprehensive overview of the nanocrystalline Al based alloys as prepared using high-energy ball milling (HEBM). It discusses the influence of HEBM parameters on grain refinement and examines methods for the consolidation of nanocrystalline Al powders; further, it reviews the effects of various processing parameters on the final microstructure and the impact of microstructure on corrosion and mechanical properties. The book also provides guidelines for choosing appropriate HEBM parameters for the production of nanocrystalline Al powders and methods for consolidating them in net-shaped components. Future challenges and possible applications of high-energy ball milled Al alloys are also discussed. The book is intended for researchers and professionals interested in aluminium alloy development, manufacturing technologies, light metals and nanocrystalline metallic materials.
Keywords: Materials science.; Renewable energy resources.; Nanoscale science.; Nanoscience.; Nanostructures.; Renewable energy sources.; Alternate energy sources.; Green energy industries.; Metals.; elektronické knihy; electronic books